Diamond Detectors for Radiotherapy X-Ray Small Beam Dosimetry - Talamonti, C.; Kanxheri, K.; Pallotta, S.; Servoli, L. (Frontiers in Physics, 2021)
Many new X-Ray treatment machines using small and/or non-standard radiation fields, e.g., Tomotherapy, Cyber-knife, and linear accelerators equipped with high-resolution multi-leaf collimators and on-board imaging system, have been introduced in the radiotherapy clinical routine within the last few years. The introduction of these new treatment modalities has led to the development of high conformal radiotherapy treatment techniques like Intensity Modulated photon Radiation Therapy, Volumetric Modulated Arc Therapy, and stereotactic radiotherapy. When using these treatment techniques, patients are exposed to non-uniform radiation fields, high dose gradients, time and space variation of dose rates, and beam energy spectrum. This makes reaching the required degree of accuracy in clinical dosimetry even more demanding. Continuing to use standard field procedures and detectors in fields smaller than 3 × 3 cm2, will generate a reduced accuracy of clinical dosimetry, running the risk to overshadowing the progress made so far in radiotherapy applications. These dosimetric issues represent a new challenge for medical physicists. To choose the most appropriate detector for small field dosimetry, different features must be considered. Short- and long-term stability, linear response to the absorbed dose and dose rate, no energy and angular dependence, are all needed but not sufficient. The two most sought-after attributes for small field dosimetry are water equivalence and small highly sensitive (high sensitivity) volumes. Both these requirements aim at minimizing perturbations of charged particle fluence approaching the Charged Particle Equilibrium condition as much as possible, while maintaining high spatial resolution by reducing the averaging effect for non-uniform radiation fields. A compromise between different features is necessary because no dosimeter currently fulfills all requirements, but diamond properties seem promising and could lead to a marked improvement. Diamonds have long been used as materials for dosimeters, but natural diamonds were only first used for medical applications in the 80 s. The availability of reproducible synthetic diamonds at a lower cost compared to natural ones made the diffusion of diamonds in dosimetry possible. This paper aims to review the use of synthetic poly and single-crystal diamond dosimeters in radiotherapy, focusing on their performance under MegaVoltage photon beams. Both commercial and prototype diamond dosimeters behaviour are described and analyzed. Moreover, this paper will report the main related results in literature, considering diamond development issues like growth modalities, electrical contacts, packaging, readout electronics, and how do they affect all the dosimetric parameters of interest such as signal linearity, energy dependence, dose-rate dependence, reproducibility, rise and decay times.